e-Resíduos: A influência da norma européia WEEE na estratégia da indústria de celulares no Brasil e no mundo e o impacto ambiental do descarte inadequado - Chrispim Neto, José Padilha (2007)
This present Thesis, is explorer work and presents an analysis of e-wastes of the industry of cellular mobile telephony, evaluating the evolution of the telecommunications nets and as if it holds the global and Brazilian market of cellular telephony. It approaches the elements gifts in the cellular devices that can badly cause to the environment and the health, the discarding of the devices in end of life cycle is made. It analyzes the new European regulation of electric equipment residues and electronic, the WEEE, as it influenced the strategy of the companies manufacturers of mobile phone cellular and of that she forms is possible to create a Brazilian national industry for recycling of devices of cellular, with conditions to globally competition. For this some possible models of being implanted in Brazil are presented. The project of law 203/91 on solid residues is argued and as it would be interesting if to persist some proposals presented to the project, to create a Brazilian market of recycling with capacity of global competition for use to advantage of the European regulation if to get a competitive advantage